2019
DOI: 10.1080/02673843.2019.1700807
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alcohol consumption and alcohol use disorders among middle and high school students in the province of Khemisset, Morocco: a cross-sectional study

Abstract: Alcohol use among adolescents remains a major public health problem. Studies carried out on alcohol use among adolescents in Morocco remain few in number. This study evaluated the prevalence of alcohol use, determinants of hazardous, harmful alcohol use or possible dependence (alcohol use disorder: AUD), and determined its predictors among middle and high school students in the province of Khemisset, Morocco. A crosssectional study conducted in public middle and high schools in the province of Khemisset, Moroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
4
4
0
Order By: Relevance
“…In this study, the prevalence of alcohol use disorder was 26.5%, the finding was supported by the study done in Colombia university students, in which 20.5% of the respondents had harmful consumption and 14.9% were at risk of dependence, 33 likewise a study done in the USA showed 18% of US college students suffered from AUD. 34 Similar findings were also reported from the studies done in Wolaita University Students and Morocco high school students 8.5%, 35 however, the finding was by far lower than the studies done in Undergraduates at English Universities, in which 61% of the students had AUD 36 and Eldoret, western Kenya 51.9%. 37 The discrepancy could be due to the variation in the study tools to assess AUD and alcohol use regulation policy differences among the countries.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, the prevalence of alcohol use disorder was 26.5%, the finding was supported by the study done in Colombia university students, in which 20.5% of the respondents had harmful consumption and 14.9% were at risk of dependence, 33 likewise a study done in the USA showed 18% of US college students suffered from AUD. 34 Similar findings were also reported from the studies done in Wolaita University Students and Morocco high school students 8.5%, 35 however, the finding was by far lower than the studies done in Undergraduates at English Universities, in which 61% of the students had AUD 36 and Eldoret, western Kenya 51.9%. 37 The discrepancy could be due to the variation in the study tools to assess AUD and alcohol use regulation policy differences among the countries.…”
Section: Discussionsupporting
confidence: 83%
“…It might be due to the fact that health problems or life events such as divorce, loss of family members, or unemployment were common among older peoples which might increase the risk of excessive alcohol drinking. The finding was similar to other studies [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our sample, the prevalence of alcohol drinking is estimated to be 13.82%, with no significant difference between genders. The same trend was observed among youth from the province of Khemisset, Morocco, where the prevalence of alcohol consumption is estimated to be 15.6% [20].…”
Section: Tobacco and Alcohol Consumptionsupporting
confidence: 69%